Technologies of the YouTuber self: digital vigilantism, masculinities and attention economy in neoliberal Japan - Demelius, Yoko; Yoshida, Yutaka (Taylor & Francis, 2025)
This paper investigates YouTube vigilantism in contemporary Japan. While studies have discussed the relationship between vigilantism and the public police and technology’s role in the weaponisation of visibility, attempts to explain the rise of such activities from the perspectives of identity and culture have been scarce. The present study addresses this by exploring vigilante YouTubers in contemporary Japan who share footage of the exposure and occasional arrest of individuals who engage in illegal or illicit activities. It applies Foucault’s technologies of the self as a theoretical framework and examines the notions of masculinity and entrepreneurship in neoliberal Japan by focusing on the conceptualisation of vigilantes’ identities using social media. The analysis reveals that vigilantes’ activities are motivated by the ambition to legitimise their masculinity, moral superiority, and respectable social roles in contemporary Japan, in which hegemonic masculinity, rigid gender-role expectations, and the concept of a well-functioning ‘proper’ society are re-negotiated.